Short Communication: Rediscovery of the Zamboanga peninsula endemic Boesenbergia longipetiolata (Ridl.) Merr. (Zingiberaceae) after a lapse of over a century, including an amended description and an updated distribution - JANNAH E. YONGCO; OLIVE A. AMPARADO; MARK ARCEBAL K. NAIVE (Society for Indonesian Biodiversity, 2023)
Abstract. Yongco JE, Amparado OA, Naive MAK. 2023. Short Communication: Rediscovery of the Zamboanga peninsula endemic Boesenbergia longipetiolata (Ridl.) Merr. (Zingiberaceae) after over a century, including an amended description and an updated distribution. Biodiversitas 24: 6305-6309. Zamboanga Peninsula is one of the important sites for biodiversity studies in the Philippines. Despite that, there have been limited attempts for field explorations focusing on the floral diversity and plant inventories in the region, resulting in the scarcity of floristic data and has left many of its plant species, including their status, unknown. Included is Boesenbergia longipetiolata, a poorly known plant species belonging to the Zingiberaceae family, endemic to the Zamboanga Peninsula, Western Mindanao, Philippines and considered a long-lost species as its existence had not been reported since it was first collected in 1909. A meticulous examination of a specimen collected from a recent botanical exploration conducted in Mount Timolan Protected Landscape of Zamboanga Peninsula in July 2022 revealed the rediscovery of B. longipetiolata after a lapse of over a century. This species is unique among all other Philippine endemic Boesenbergia species by having a very long petiole and is closely similar to the Malay Peninsula endemic B. longipes but differs significantly by having lower stature, narrowly ovate to lanceolate lamina, a longer calyx and a slender corolla tube. In this study, an amended taxonomic description, including information on its geographical distribution and habitat, and a proposed conservation status are provided.